Cell segregation, mixing, and tissue pattern in the spinal cord of the xenopus laevis neurula. Issue 10 (5th August 2013) - Edlund, Anna F.; Davidson, Lance A.; Keller, Raymond E.
<x xml:space="preserve">Abstract</x> Background: During Xenopus laevis neurulation, neural ectodermal cells of the spinal cord are patterned at the same time that they intercalate mediolaterally and radially, moving within and between two cell layers. Curious if these rearrangements disrupt early cell identities, we lineage‐traced cells in each layer from neural plate stages to the closed neural tube, and used in situ hybridization to assay gene expression in the moving cells. Results: Our biotin and fluorescent labeling of deep and superficial cells reveals that mediolateral intercalation does not disrupt cell cohorts; in other words, it is conservative. However, outside the midline notoplate, later radial intercalation does displace superficial cells dorsoventrally, radically disrupting cell cohorts. The tube roof is composed almost exclusively of superficial cells, including some displaced from ventral positions; gene expression in these displaced cells must now be surveyed further. Superficial cells also flank the tube's floor, which is, itself, almost exclusively composed of deep cells. Conclusions: Our data provide: (1) a fate map of superficial‐ and deep‐cell positions within the Xenopus neural tube, (2) the paths taken to these positions, and (3) preliminary evidence of re‐patterning in cells carried out of one environment and into another, during neural morphogenesis. Developmental Dynamics, 242:1134–1146, 2013. © 2013 Wiley Periodicals, Inc.